The role of the vagus nerve in appetite control: implications for the pathogenesis of obesity - Cork,SC (Journal of Neuroendocrinology, 2018)
The communication between the gut and the brain is important for the control of energy homeostasis. In response to food intake, enteroendocrine cells secrete gut hormones which ultimately suppress appetite through centrally-mediated processes. Increasing evidence implicates the vagus nerve as an important conduit in transmitting these signals from the gastrointestinal tract to the brain. Studies have demonstrated that many of the gut hormones secreted from enteroendocrine cells signal through the vagus nerve, and the sensitivity of the vagus to these signals is regulated by feeding status. Furthermore, evidence suggests that a reduction in the ability of the vagus nerve to respond to the switch between a "fasted" and "fed" state, retaining sensitivity to orexigenic signals when fed or a reduced ability to respond to satiety hormones, may contribute to obesity. This article is protected by copyright. All rights reserved.